Standard specification for Steel Castings, Carbon, Suitable for fusion welding, for high-temperature service. (American Society for Testing and Materials, 2008)
This specification2 covers carbon steel castings for valves, flanges, fittings, or other pressure-containing parts for high-temperature service and of quality suitable for assembly with other castings or wrought-steel parts by fusion welding.